Lightning electromagnetics - Cooray, Vernon (The Institution of Engineering and Technology, 2012)
This book has 25 chapters and discusses the following topics: lightning electromagnetics; electromagnetic theory; electromagnetic fields; accelerating charge; propagating current pulse; discharge process in the atmosphere; nonthermal electrical discharges in air; charging process in clouds; lightning flash development; return stroke model; engineering applications; electromagnetic models; antenna model; method of moments; transmission line models; electric and magnetic fields over finitely conducting ground; Sommerfeld's integrals; Schumann resonances; mesosphere; ionosphere; magnetosphere; overhead and underground cables; lightning transients in power systems; attachment of lightning flashes to grounded structures; generation in corona, streamer and low-pressure electrical discharges; production; high energetic radiation; thunderstorms; visual sensory experience excitation; and modelling lightning strikes to tall towers.